Relation between selected attributes of the perception space and the evaluation of sound - HOJAN, E.; FURMANN, A. (Archives of Acoustics, 1991)
The aim of the presented investigations was to determine the relations between the selected attributes of sound perception space and the subjective evaluation of sound "fidelity". Each sound examined was evaluated twice: for its "fidelity" with respect to the mental model and for the attributes of sound perception space ("clearness", "fullness", "spaciousness", "sharpness", "loudness", "lack of distortions"). We examined test signals (pink noise, white noise, speech signal and a musical piece) filtered by five kinds of filters and reproduced by a loudspeaker system. Hi-fi experts acted as subjects. Analysis of the results showed that "fullness", "sharpness" and "lack of distortions" determine the values of the subjective evaluation of sound "fidelity" when "fidelity" is evaluated with respect to a mental model.